Food testing working with Yeast - Ansell, Key; Video Educational Australasia (Australia : Video Educational Australasia, 1998)
This program look more closer at Yeast, its biology, its history and the necessary conditions for its growth. Also demonstrate the effects of using dried and compressed yeast in the making of bread rolls in a real-life school laboratory environment
Title from title screen
Executive producer, Neil Barrett ; editor, Sasha Trikojus
Keywords: Yeast; Yeast -- Physiology; Yeast fungi